Usage of source separated urine for the biodiesel production from algal biomass - Tunay, Dogukan; Altinbas, Mahmut; Ozkaya, Bestami (ELSEVIER, 2022)
Urine is one of the most significant side-stream of domestic wastewater and this highly concentrated wastewater can be used as a growth medium for microalgae for the purpose of biodiesel production. In this study, auto-trophic microalgae cultivation was achieved with changing dilutions of 5%, 10%, 20% and 40% (v/v). The highest biomass production was carried out with 5% of urine including medium as 1 g/L after the three sets of acclimation with increasing volumes. At the beginning of the microalgae cultivation, biomass productivity and nutrient accumulation was considerably low. However, biomass productivity was doubled after the acclimation studies with 23% of lipid content. During the cultivation ammonium nitrogen was treated more than 90% and the phosphorus removal was maximum 58%. Fatty acids and methyl esters (FAME) content of the biomass oil was showed the high quality of biodiesel production was possible with 33.01 +/- 1.02% of saturated fatty acids and 86.62 +/- 3.29% of C16-C18 fatty acids. Urine has high potential to be used for microalgae cultivation and the biodiesel production.
Keywords: Urine; Renewable energy; Biodiesel; Fatty acids; Algal biomass; FATTY-ACID-COMPOSITION; NUTRIENT RECOVERY; WASTE-WATER; CHLORELLA-PROTOTHECOIDES; PHOSPHORUS REMOVAL; MICROALGAE; CULTIVATION; GROWTH; NITROGEN; PLATENSIS; Biotechnology & Applied Microbiology; Engineering